Pengaruh Discount Dan Live Streaming Terhadap Impulsive Buying : Suatu Studi Pada Konsumen Produk Online Shop Berhijab.co Di Lumbung - Megarista Agustin; Nana Darna; Kasman Kasman (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Assessment of success in achieving high sales targets for a company can be measured from the increase in impulsive buying. To achieve impulse buying behavior, companies must consider factors that can influence this behavior, such as dscount and live streaming. The purpose of this research is to determine the effect of discounts on impulsive buying among consumers of Berhijab.co online shop products in Lumbung, the influence of live streaming on impulsive buying among consumers of Berhijab.co online shop products in Lumbung, as well as the influence of discounts and live streaming on impulsive buying in consumers of Berhijab.co online shop products in Lumbung. This research method uses a survey method with a quantitative approach. The population of this research is consumers of the online shop Berhijab.co. The sampling technique was carried out using a non-probability random sampling method, data was collected by distributing questionnaires to 98 respondents. Data analysis was carried out using simple correlation coefficient analysis, multiple correlation coefficient analysis, coefficient of determination, multiple linear regression analysis, t test, and F test. The results of this study show that: the effect of discounts on impulsive buying is high, the effect of live streaming on impulsive buying is high and The influence of discounts and live streaming on impulsive buying is high.